Divergência genética de linhagens de feijão-mundo (Vigna radiata (L.) Wilczeck) - MIRANDA, GLAUCO VIEIRA; COELHO, ANTONIO DANIEL FERNANDES; SHIMOYA, ALDO; COIMBRA, RONALDO RODRIGUES; SANTOS, IZABEL CRISTINA DOS (Revista Ceres, 2015)
.